Wieczność jako niezgoda: Stein, Levinas, Ricoeuer - Loba, Mirosław (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2018)
SummaryIn this contribution I try to show how E. Stein, E. Levinas and P. Ricoeurexpress their disagreement with Heideggerian conception of being-towards-death and propose their vision of eternity and its experience. The three main images are commented:the death as a discontinuity and condition of a new life, suspension of the time to the resurrection by the other, the intensification of the experience of time.